The haemodynamic and cardiovascular effects of dialysis - Selby, Nicholas Michael (2007)
Patients on dialysis are subject to hugely elevated rates of cardiovascular mortality. This thesis describes research work focusing on the large scale haemodynamic changes that occur during dialysis and how they may negatively impact on the cardiovascular system. Our results show that the haemodynamic disturbances that occur during haemodialysis are of sufficient magnitude to cause left ventricular (LV) regional wall motion abnormalities, reflecting subclinical myocardial ischaemia (myocardial stunning). This is pertinent as in non-dialysis patients repeated episodes of myocardial stunning lead to chronic heart failure, and in dialysis patients the presence of LV dysfunction dramatically increases the risk of death. We also explore how the haemodynamic effects of dialysis and the genesis of LV regional wall motion abnormalities can be ameliorated by using various interventions comprising of biofeedback dialysis (Hemocontrol and Diacontrol), cooling the dialysate and acetate free paired haemodiafiltration (PHF). We also examine the haemodynamic and metabolic effects of peritoneal dialysis (both continuous ambulatory and automated peritoneal dialysis) and show that these are much greater than previously thought. We also investigate possible mechanisms underlying these changes, namely alterations in cardiac filling and systemic glucose absorption leading to hyperinsulinaemia, and go on to examine the differential effects of the commercially available peritoneal dialysis solutions. Finally, we examine whether regional LV function is affected by the haemodynamic changes of CAPD.